Power quality assessment of grid-connected wind farms considering regulations in turkey - Kocatepe, Celal; Inan, Asian; Arikan, Oktay; Yumurtaci, Recep; Kekezoglu, Bedri; Baysal, Mustafa; Bozkurt, Altug; Akkaya, Yener (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
This paper presents measurement system and detailed analysis of power quality at the substation of two different wind farm sites which are of low and high power rate. Measurement system has been designed using a data acquisition board (DAQ), Labview software, Matlab programming and a portable PC. The system has been installed at medium voltage level at substation of both wind farms. The real measurement results at substations are compared to current regulations in Turkey. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Wind power; Power quality; Harmonics; Flicker; Voltage unbalance; Science & Technology - Other Topics; Energy & Fuels